The Connection of Study Abroad to Students' Positive Feelings of Institutional Action. (November 2019) - Di Maggio, Lily M.
Previous empirical inquiry into study abroad has consistently shown that students who study abroad have higher graduation rates than students who do not study abroad. In the current study, it was theorized that study abroad increased students' perceptions of the college or university that they attended. Using data from the National Survey of Student Engagement, the supportive campus environment scores of students who studied abroad were compared with students who did not study abroad. The measurement of supportive campus environment was shown to be consistent to measuring students' perception of Tinto's concept of institutional action. The current study controlled for race/ethnicity, gender, and major. The findings indicated that students' feelings of institutional action were more positive if they studied abroad; however, there was some variance based on academic major and race/ethnicity. At the end of the current study, policy implications were given related to the findings, and ideas for further research were presented.